PEMBANGUNAN WILAYAH DENGAN PEMETAAN POTENSI SEKTOR PERKEBUNAN UNTUK PERTUMBUHAN EKONOMI KABUPATEN OKU (JASEP, 2020)
This study is to analyze regional development by mapping the potential of the plantation sector to increase economic growth in OKU Regency. The purpose of analyzing this research is to determine which districts have the potential for basic plantation crops in OKU district so that the formulation of regional development will be right on target. The research method uses a purposive method which is carried out on purpose. Meanwhile, the research data used secondary data obtained from related agencies. To analyze the data, use the location quotient (LQ) where the mapping was carried out on the time series data from 2017 to 2019. The results of this study provide an overview of the potential of each sub-district that has a sub-sector of the plantation plant base. Mapping the potential of the plantation sector was analyzed using 2 variables, namely planting area and production. In the planting area of LQ> 1, the highest ranking was made with the highest LQ value, namely the highest consecutive ulu ogan, sosoh buay termites, West Baturaja, muara jaya, lubuk raja. Whereas the highest LQ production was Ulu Oggan sub-district, namely 16.64 coconut commodities, 9.50 termite buoys for cocoa, West Baturaja 6.17 palm oil, a field of coffee and pepper, 2.66 and 3.63 and East Baturaja namely 1.74 rubber plants. Keyword: Mapping, Development, Plantation Agriculture, Territory